2007
DOI: 10.3102/0002831207308221
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Professional Development Effective? Strategies That Foster Curriculum Implementation

Abstract: This study uses a sample of 454 teachers engaged in an inquiry science program to examine the effects of different characteristics of professional development on teachers’ knowledge and their ability to implement the program. The authors analyzed results from a survey of teachers served by 28 professional development providers within a hierarchical linear modeling framework. Consistent with findings from earlier studies of effective professional development, this study points to the significance of teachers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
702
2
24

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 906 publications
(783 citation statements)
references
References 50 publications
21
702
2
24
Order By: Relevance
“…We asked teachers to identify the importance of each of seven types of barriers derived from earlier evaluation studies of the GLOBE program (Penuel et al, 2007). These barriers were difficulty finding time to prepare for implementing GLOBE, lack of technology access, lack of technical support for using computers and software, lack of GLOBE equipment, unsupportive school building administrators, and unsupportive district administrators.…”
Section: Perceptions Of Alignment Of Globe With Alabama Course Of Stumentioning
confidence: 99%
See 1 more Smart Citation
“…We asked teachers to identify the importance of each of seven types of barriers derived from earlier evaluation studies of the GLOBE program (Penuel et al, 2007). These barriers were difficulty finding time to prepare for implementing GLOBE, lack of technology access, lack of technical support for using computers and software, lack of GLOBE equipment, unsupportive school building administrators, and unsupportive district administrators.…”
Section: Perceptions Of Alignment Of Globe With Alabama Course Of Stumentioning
confidence: 99%
“…We incorporated into our questionnaire a six-item factor (α = .93) used in two earlier studies of professional development (Garet et al, 2001;Penuel et al, 2007), which measures how well the professional development matched the teacher's goals for professional development, the existing reform ideas within the school, and whether the professional development was followed up with activities that built upon what was already learned. In this study, we used alignment to teacher and organizational goals as a measure of the effects of different policy tools on teachers' perceptions of the importance of the GLOBE program.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Um dos efeitos da colaboração entre professores é o impacto na incerteza sentida relativamente ao trabalho, a qual, quando experienciada a sós, pode enfraquecer o sentimento de confiança. Daí que os professores que trabalham em colaboração conseguem mais facilmente proceder a levantamento e exploração de problemas ou dilemas identificados pelos próprios professores (PENUEL et al, 2007).…”
Section: Contributo Da Colaboração Para O Desenvolvimento Profissionalunclassified
“…O trabalho colaborativo, a partir da discussão e partilha de ideias, tende a aumentar o grau de motivação dos professores, incentivando-os a um maior envolvimento na aproximação de novo conhecimento pedagógico-didático do conteúdo e na resolução de problemas (ROL-DÃO, 2007). Daí a importância do trabalho colaborativo para os professores, tendo em conta que este permite a aquisição de novas aprendizagens e a resolução de problemas que se confrontam todos os dias (PENUEL et al, 2007).…”
Section: Introductionunclassified
“…They also found that such structural features as the form of the activity, collective participation, and duration of the activity have indirect effects on teacher learning through these core features. Built from the theoretical constructs employed by Garet et al (2001), Penuel, Fishman, Yamaguchi, andGallagher (2007) added the role of context as an important consideration in science education professional development. They noted that participants bring their given contexts to professional development and contextual elements such as school philosophies, prioritized initiatives, planning time, and availability of materials can impact a teacher's application of a new innovation.…”
Section: Literature Reviewmentioning
confidence: 99%